Neuroblastoma‐secreted exosomes carrying miR‐375 promote osteogenic differentiation of bone‐marrow mesenchymal stromal cells. Issue 1 (3rd June 2020) - Colletti, Marta; Tomao, Luigi; Galardi, Angela; Paolini, Alessandro; Di Paolo, Virginia; De Stefanis, Cristiano; Mascio, Paolo; Nazio, Francesca; Petrini, Stefania; Castellano, Aurora; Russo, Ida; Caruso, Roberta; et al.
ABSTRACT: Bone marrow (BM) is the major target organ for neuroblastoma (NB) metastasis and its involvement is associated with poor outcome. Yet, the mechanism by which NB cells invade BM is largely unknown. Tumour microenvironment represents a key element in tumour progression and mesenchymal stromal cells (MSCs) have been recognized as a fundamental part of the associated tumour stroma. Here, we show that BM‐MSCs isolated from NB patients with BM involvement exhibit a greater osteogenic potential than MSCs from non‐infiltrated BM. We show that BM metastasis‐derived NB‐cell lines secrete higher levels of exosomal miR‐375, which promotes osteogenic differentiation in MSCs. Of note, clinical data demonstrate that high level of miR‐375 correlates with BM metastasis in NB patients. Our findings suggest, indeed, a potential role for exosomal miR‐375 in determining a favourable microenvironment in BM to promote metastatic progression. MiR‐375 may, thus, represent a novel biomarker and a potential target for NB patients with BM involvement.